Rethinking COVID-19 Vulnerability: A Call for LGBTQ+ Im/migrant Health Equity in the United States During and After a Pandemic (Mary Ann Liebert, 2020)
Public health responses to the coronavirus disease 2019 (COVID-19) pandemic have emphasized older adults' vulnerability, but this obfuscates the social and political root causes of health inequity. To advance health equity during a novel communicable disease outbreak, public health practitioners must continue to be attentive to social and political circumstances that inform poor health. Such efforts are especially needed for populations who are exposed to numerous social and political factors that structure health inequity, such as lesbian, gay, bisexual, transgender, or otherwise-queer identifying (LGBTQ+) populations and im/migrant populations. The COVID-19 outbreak is, therefore, a critical time to emphasize root causes of health inequity.